Evaluasi Mutu Pada Proses Pengelasan Menggunakan Metode Old dan New Seven Tools di PT. XYZ - Dwi Putri Fajar; Deny Andesta (Fakultas Teknik, 2023)
In the service and manufacturing industry competition, companies need to maintain the quality of the products they produce. PT XYZ is a company engaged in steel fabrication work services. Fabrication work there is a sequence of production processes that must be maintained in quality, because the company must do the work with the standards set by the clients. One of the most influential production processes in quality control is the welding process. This study aims to evaluate the quality of the welding process of the cable tray support project consisting of four batches. The results of the study found six types of welding defects, namely porosity, incomplete fushion, over spatter, overlap, slag, and undercut. Based on the Pareto diagram, there are 2 types of welding defects that will be prioritized, namely porosity and over spatter. Furthermore, based on the results of processing the new seven tools, it can be seen that the most important factor causing defects is the Man factor because this factor is also closely related to the Methode factor. alternative improvements that will be prioritized first because they have the highest value are conducting training to the welder to the maximum, conducting stricter supervision by the welding supervisor to workers when welding, the welding supervisor conducts regular machine supervision, scheduling maintenance on the machine by quality control.